Bantuan Pemerintah dan Eksistensi Industri Rumah Tangga Pembuat Kembang Rampai di Kecamatan Abiansemal Kabupaten Badung - Prabhandina, A.A. Ayusya; Tisnawati, Ni Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 5, Mei 2017 (pp. 677 - 919), 2017)
Home industry kembang rampai has a great potential to be developed in Bali because it is dominated by Hindu comunity. Kembang rampai used as a components for offerings in religious activities. This study is aimed to analyze the effect of capital, labor, land and government assistance simultaneously and partially to income of home industry kembang rampai in Abiansemal District, Badung Regency. The number of samples in this study are 80 business units that determined by Proportionate Stratified Random Sampling. Data analysis technique that is used is multiple linear regression with dummy as independent variables. The study states that capital, labor, land and government assistance simultaneously effect on income of home industry kembang rampai. Partially capital, land and government assistance positive and significant effect on income income of home industry kembang rampai. While labor is not significant effect partially on income.
Keywords: modal, tenaga kerja, luas lahan, bantuan pemerintah, pendapatan